Estrategias de marketing y el posicionamiento en el mercado de la empresa “San Rene” en Esmeraldas. - Bautista Medranda, Juan Francisco (2025)
The research is based on the approach of marketing strategies and positioning of the cocoa of the company San René. The problem arises from the need to find solutions to establish and determine such strategies, with the aim of improving their market presence. A general hypothesis is put forward that states that marketing strategies have an impact on the positioning of the product in the Esmeraldas market, while the null hypothesis suggests the opposite. The objectives of the research include determining the marketing management strategies for the market positioning of the San René company. The methodology used is non-experimental, using questionnaires as a data collection tool. The conclusion reveals that the San René company has a strong position in the Esmeraldas market, supported by brand recognition and efficient production and distribution. However, challenges are identified such as the limited perception of brand sustainability, which is why the recommendations suggest conducting a detailed analysis of the brand image, exploring new markets, developing new products to drive growth and improve the market presence of the San René company.